2021
DOI: 10.2166/wst.2021.627
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of magnetic copper ferrite nanoparticle as peroxymonosulfate activating catalyst for effective degradation of levofloxacin

Abstract: The magnetic CuFe2O4 nanoparticles were successfully synthesized with a coprecipitation method at 500 °C calcination temperature, which were utilized to degrade levofloxacin (LEV) as peroxymonosulfate (PMS) activator. The structure and composition of nanocatalyst were characterized by a series of methods, including Scanning electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, Vibrating sample magnetometer and Thermogravimetric analysis. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…This further indicated that CoFe@CSC-700 has good reusability and high water stability in the PMS reaction system and has strong potential for environmental applications. Table S1 listed the performance comparison of CoFe@CSC-700 with other previously reported catalysts for LEV degradation [46][47][48][49][50][51][52]. As can be seen from Table S1, CoFe@CSC-700 was able to achieve a higher LEV removal rate in a shorter period at a lower catalyst dosage and PMS concentration than the catalysts prepared in other studies, suggesting that the catalyst has superior performance and greater potential application prospects for treating LEV pollution in water.…”
Section: Evaluation Of the Stability And Performance Of Cofe@csc-700mentioning
confidence: 84%
“…This further indicated that CoFe@CSC-700 has good reusability and high water stability in the PMS reaction system and has strong potential for environmental applications. Table S1 listed the performance comparison of CoFe@CSC-700 with other previously reported catalysts for LEV degradation [46][47][48][49][50][51][52]. As can be seen from Table S1, CoFe@CSC-700 was able to achieve a higher LEV removal rate in a shorter period at a lower catalyst dosage and PMS concentration than the catalysts prepared in other studies, suggesting that the catalyst has superior performance and greater potential application prospects for treating LEV pollution in water.…”
Section: Evaluation Of the Stability And Performance Of Cofe@csc-700mentioning
confidence: 84%
“…The synthesis of mesoporous CuFe 2 O 4 powder was carried out by a procedure as described in a previous work [ 16 ] , but without annealing at high temperature due to some modification. Briefly, mixed reagents of Fe 2 (SO 4 ) 3 and CuSO 4 .5H 2 O (analytical reagent, purchased from Xilong Scientific Co.) were vigorously stirred in distilled water to obtain 100 mL solution containing Fe 3+ ion (20 mmol) and Cu 2+ ion (10 mmol).…”
Section: Methodsmentioning
confidence: 99%